Diplodia natalensis, pole evans y Phytophthora spp. sobre citricos cubanos - Rodriguez Torres, J.
(Es, En)
Ilus., 10 ref.
Keywords: CITRUS; ENFERMEDADES FUNGOSAS; DIPLODIA NATALENSIS; PHYTOPHTHORA; SINTOMAS; CUBA; POLE EVANS